Visual Studio 2012 cookbook : 50 simple but incredibly effective recipes to immediately get you working with the exciting features of Visual Studio 2012 /: 50 simple but incredibly effective recipes to immediately get you working with the exciting features of Visual Studio 2012. (2012) - Unknown
No abstract available